2017
DOI: 10.1186/s12985-017-0786-5
|View full text |Cite
|
Sign up to set email alerts
|

Outbreak tracking of Aleutian mink disease virus (AMDV) using partial NS1 gene sequencing

Abstract: BackgroundAleutian Mink Disease (AMD) is an infectious disease of mink (Neovison vison) and globally a major cause of economic losses in mink farming. The disease is caused by Aleutian Mink Disease Virus (AMDV) that belongs to the genus Amdoparvovirus within the Parvoviridae family. Several strains have been described with varying virulence and the severity of infection also depends on the host’s genotype and immune status. Clinical signs include respiratory distress in kits and unthriftiness and low quality o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 26 publications
1
24
0
Order By: Relevance
“…Total DNA was extracted using the QIAmp®DNA Mini Kit with the Standard version 1 protocol automated on the QIAcube (Qiagen, Copenhagen, Denmark). PCR and Sanger sequencing was carried out as previously described [ 11 ]. The sequences names were tagged “f” or “w” to indicate if the mink was farmed or wild respectively, and included the country and region of sampling, and the sampling date as follows: AMDV_mink-f/w_Country_unique identifier_sampling date.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Total DNA was extracted using the QIAmp®DNA Mini Kit with the Standard version 1 protocol automated on the QIAcube (Qiagen, Copenhagen, Denmark). PCR and Sanger sequencing was carried out as previously described [ 11 ]. The sequences names were tagged “f” or “w” to indicate if the mink was farmed or wild respectively, and included the country and region of sampling, and the sampling date as follows: AMDV_mink-f/w_Country_unique identifier_sampling date.…”
Section: Methodsmentioning
confidence: 99%
“…The partial NS1 sequencing of viruses from this outbreak revealed that the outbreaks were caused by two distinct viral strains, which clearly deviated from all viruses involved in previously known outbreaks in Denmark [ 11 ]. Furthermore, there was only limited nucleotide sequence homology to any AMDV sequences in GenBank.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Phylogenetic analysis was carried out in MEGA6. A phylogenetic tree was obtained by the Maximum Likelihood method with 1000 bootstrap replications for the sequence coding NS1 protein as this fragment has been used to analysis of relationships between isolates and tracing of outbreaks [13,14].…”
Section: Evaluation Of the Specifi City Of The Reactionmentioning
confidence: 99%
“…Electrophoretic separation of PCR products: M -100 bp marker, reaction results for samples isolated from blood tested as individual samples (wells 1-4), pooled blood(5)(6)(7)(8) and spleens(9)(10)(11)(12)(13)(14)(15)(16) …”
mentioning
confidence: 99%